Blockbusting and the challenges faced by black families in building wealth through housing in the postwar United States - Daniel Hartley; Jonathan Rose (Federal Reserve Bank of Chicago, 2023)
We study the impacts of blockbusting, i.e. large-scale racial turnover of urban neighborhoods orchestrated by real estate professionals using aggressive and discriminatory practices. In a panel of census tracts across large cities in the postwar United States, we compare tracts subjected to blockbusting activity to similar neighboring tracts not subjected to blockbusting. We find that blockbusting caused substantially lower house values over the next few decades. To understand the mechanisms behind this effect, we analyze property-level data in one neighborhood of Baltimore, Maryland. We find that new residents that purchased their properties through blockbusters were charged higher prices and had higher foreclosure rates than new residents that purchased directly from existing property owners.
Keywords: N22; N92; G21; R23; R51; 330; blockbusting; wealth gap; housing finance discrimination